Pelatihan Tanggap Darurat Bencana Dalam Meningkatkan Pengetahuan Mitigasi Bencana Pada SD Aisyiyah Kamila Malang - Erlya Alberta, Rena; Mishbah Ulayya, Falihah; Nisella Salsabila, Nazwa; Nuramdani, Sofitria; Nasaroh, Nabilatun; Putri Prameswari, Sekar Arum; Islami, Salma Fadia; Suprobo, Nina Rini (DHARMA BAKTI, 2024)
Indonesia, located along the Pacific Ring of Fire, is vulnerable to natural disasters such as earthquakes and floods. Malang City, as one of the regions with a high risk of disasters, has experienced an increase in earthquake and flood incidents that threaten the safety of its residents and infrastructure. Therefore, disaster preparedness education in elementary schools is crucial to enhancing students' readiness in the face of disasters. This community service activity was conducted on May 17, 2024, at SD Aisyiyah Kamila Malang, involving 43 fourth-grade students. The aim of the activity was to improve students' knowledge and skills regarding disaster preparedness. The methods employed included socialization, demonstrations, and practical simulations. Data and feedback were collected through pre-tests and post-tests to assess the students' understanding. The pre-test was administered before the activity to measure their initial knowledge, while the post-test was given after the activity to evaluate any changes in knowledge. The evaluation results indicated a significant improvement in students' knowledge, from the "sufficient" category to the "good" category, with paired sample T-test results showing statistical significance (p<0.05). Additionally, the students showed high enthusiasm and a strong understanding during the simulation. This program supports the third and fourth SDGs, aiming to ensure healthy lives and promote well-being for all individuals of all ages.